On the Contributions of the Northeast Cold Vortex to the Formation and Evolution of Backflow Blizzard - Yan, Qi; Cui, Jin; Tan, Zhenghua; He, Bao-Jie (Frontiers in Earth Science, 2022)
Blizzard is a severe weather-related disaster with significant environmental, economic and social impacts. Moreover, the blizzard is increasingly frequent along with climate change. Therefore, an accurate estimation of blizzards is important to enhance resilience. However, blizzard formation and types vary with geographic characteristics (e.g. ocean, terrain, latitude). Previous studies have not well presented the backflow blizzard in Northeast China, associated with the cold vortex. To overcome this research gap, this paper aims to analyze the characteristics of a backflow blizzard in Liaoning, China, and reveal the reasons behind the spatial heterogeneity of snowstorm intensity. With the support of observation data and mesoscale numerical simulation, this study pointed out that the northeast cold vortex, caused by airflows from the Sea of Japan transported by the easterly airflow, the East China Sea and the Yellow Sea transported by the southeast airflow, and the low-level southwest airflow, was an important driver to the blizzard. Moreover, it was the interactions of airflow movement, water vapor variation, and frontogenesis occurrence at different layers that caused the differences in snowfall intensity, duration, and volume at Zhangwu and Huanren stations. Overall, this paper is of importance to provide a reference for the understanding of the backflow blizzard and its mechanism. Moreover, it is conducive to the accurate estimation of backflow blizzard, a typical snowfall type in Northeast China.